PENGAKTIFAN GERAKAN SAYANG IBU (GSI) - Unggul Priyadi (UII, 2013)
In the hamlet Krajan was there an umbrella organization of mothers in the village.The organization calledGerakan Sayang Ibu (GSI). However, the activities carried outwithin the organization has not only centered on the routine and toddlers examination.There are no activities that involve the active participation of mothers Krajan village.The program aims to reactivate and provide regular activities for members of the GSI,GSI so that members have a beneficial activity and increase knowledge for mothersKrajan village. The program begins by identifying the number of members of GerakanSayang Ibu (GSI) followed by counseling related to femininity. The results achieved inthis program is the implementation of a program that reactivate Loving MotherMovement (GSI). Besides members of the GSI have additional activities that are usefuland increase knowledge for mothers Krajan village.